Respuesta :

It’s A, as you can tell from my picture
Ver imagen Isa8484

Answer:

A

Step-by-step explanation:

let y = f(x) and rearrange making x the subject, that is

y = [tex]\frac{19}{x^3}[/tex] ( multiply both sides by x³ )

yx³ = 19 ( divide both sides by y )

x³ = [tex]\frac{19}{y}[/tex] ( take the cube root of both sides )

x = [tex]\sqrt[3]{\frac{19}{y} }[/tex]

Change y back into terms of x, thus

[tex]f^{-1}[/tex](x ) = [tex]\sqrt[3]{\frac{19}{x} }[/tex] = [tex]\frac{\sqrt[3]{19} }{\sqrt[3]{x} }[/tex] → A